Management of valvular heart disease in the pregnant patient. (2nd August 2020) - Hutt, Erika; Desai, Milind Y.
ABSTRACT: Introduction: Among cardiovascular disease in pregnancy, valvular heart disease remains a prevalent cause of maternal and fetal morbidity. The physiological changes of pregnancy can lead to decompensation of known or silent valvular heart disease. This poses a challenge to both physicians and patients in determining the best timing and management of valvular disease in the pre and post conception settings. This condition requires specific care to minimize both maternal and fetal morbidity and mortality. Areas covered: In this article, we review the recommended management of valvular heart disease in pregnancy, which include stenotic lesions, regurgitant lesions and prosthetic valves. Expert opinion: Overall, left sided stenotic lesions are poorly tolerated and require intervention prior to pregnancy in cases of severe or symptomatic stenosis. Regurgitant lesions, isolated right sided lesions and bioprosthetic valves are better tolerated. Mechanical valves pose a challenging scenario given the high risk for valve thrombosis which must be balanced with the risk of bleeding and fetal embryopathy. Shared decision making is primordial in choosing the anticoagulant strategy during pregnancy in patients with mechanical valves.